Adherence to treatment in a Western European paediatric population with haemophilia: reliability and validity of the VERITAS‐Pro scale. (26th May 2014) - Lock, J.; Raat, H.; Duncan, N.; Shapiro, A.; Beijlevelt, M.; Peters, M.; Tamminga, R. Y. J.; Leebeek, F. W. G.; Moll, H. A.; Cnossen, M. H.
Summary Treatment adherence in haemophilia is strongly associated with quality of life and the cost–benefit of treatment. Therefore, it is important to quantify and monitor it. This study aimed to validate a translation of the VERITAS‐Pro cross‐culturally and analyse treatment adherence in a Dutch population of paediatric haemophilia patients. Children aged 1–18 years with haemophilia were included from three Haemophilia Treatment Centres, on prophylactic clotting factor replacement therapy for more than 1 year. Parents and adolescents were analysed separately. The adherence scale for prophylactic therapy (VERITAS‐Pro) was translated according to international guidelines. This instrument contains a total of six subscales ('Time', 'Dose', 'Plan', 'Remember', 'Skip' and 'Communicate') each with four items. Lower scores reflect higher adherence. Overall response rate was 85%, leading to a study population of 60 children. Mean age was 10 years (SD 4.1). Internal consistency reliability: Mean Cronbach's alphas were adequate (>0.70) for total score and the subscales 'Skip' and 'Communicate'. Item‐own subscale correlations were stronger than most item‐other subscale correlations. Convergent validity: Total scores were higher for non‐adherent participants compared with adherent participants according to patient infusion logs (n = 48; P < 0.05). Test–retest correlations: Significant for all scales except 'Dose' (n = 58; P < 0.01). This study demonstrates applicability of VERITAS‐Pro outside the United States, as total score and most subscales effectively quantified treatment adherence in a Dutch paediatric population on prophylactic therapy. Non‐adherent respondents' total scores were significantly higher, demonstrating the ability of VERITAS‐Pro to identify non‐adherent individuals.